VILLAGE FUND ALLOCATION POLICY ON THE DEVELOPMENT OF THE BASIS ECONOMIC SECTOR IN THE VILLAGE: A CASE STUDY OF SOME VILLAGES IN LEBATUKAN DISTRICT OF LEMBATA REGENCY, INDONESIA - Sinu I.; Klau F.; Abdurrahman M.; Nendissa D.R. (Russian Journal of Agricultural and Socio-Economic Sciences, 2022)
The Village Fund policy in the context of community empowerment is primarily emphasized on giving trust to the poor to manage their own household economy. The central government's policy of allocating a number of budgets directly to villages to be managed provides convenience for the government and village communities to optimize the potential of their resources. This research is directed to examine models of village community empowerment with the support of the Village Fund, and to analyze the effect of program realization on strengthening the leading sector in the village. The village government of Hadakewa and Dikesare manages Village Funds with a self-management pattern to empower their potential, create jobs and encourage residents to open their own jobs. Policy, planning, implementation, evaluation are all arranged with the community. As suggested in the Village Fund management manual that with a self-management pattern, it means that the planning and implementation of these activities is carried out independently by the village. The management of village funds in the villages of Hadakewa and Dikesare succeeded in creating a village economic base that sided with the poor, bringing the poor in both villages out of the cycle of poverty that was passed down from generation to generation. BUMDes, the institution entrusted with managing village finances, continues to experience capacity building. This fact is also the target of the central government to allocate village funds to villages. The Development Economics approach which emphasizes the importance of institutional development for effective functioning of the market should also be developed in laying the foundation for development policy making. BUMDes, which is highly expected to have a presence in the village, must be a concern for the village government and village communities for the sustainability of the development that is currently running dynamically.